Slip along the San Andreas fault associated with the great 1857 earthquake - Sieh, Kerry (2013)
Historical records indicate that several meters of lateral slip along the San Andreas fault accompanied the great 1857 earthquake in central and southern California. These records, together with dendrochronological evidence, suggest that the rupture occurred along 360 to 400+ km of the fault, including several tens of kilometers of the currently creeping reach in central California. Geomorphic expressions of late Holocene right-lateral offsets are abundant along the 1857 rupture. Along 300 kilometers of the 1857 rupture, between Cholame and Wrightwood, the youngest discernible offset ranges from 3 to 9 1/2 meters. Dormancy of the fault since 1857 almost certainly indicates that this latest offset was created in 1857. Fault slip apparently associated with the 1857 earthquake varies in a broadly systematic way along the trace of the fault. It is relatively uniform along each of several long segments, but changes rather abruptly in value between these segments. This nonuniform displacement pattern may imply that some segments of the fault rupture more frequently or experience a slower long-term slip rate than others. The 1857 offsets indicate a seismic moment, mo, between 5.3 and 8.7 × 10^27 dyne-cm, assuming a 10- to 15-km depth of rupture and relatively uniform slip as a function of depth. A comparison with the rupture length, average slip value, and tectonic setting of the California earthquake of 1906 (Ms = 8 1/4)indicates a value of M = 8 1/4 + for the 1857 event.